Cardiac rehabilitation for coronary artery disease: latest updates. (23rd September 2021) - Epstein, Elizabeth; Maisel, Sofie; Maysent, Kathryn; Taub, Pam R.
Abstract : Purpose of review: To summarize recent innovations in cardiac rehabilitation and provide a view towards the future of cardiac rehabilitation as it adjusts to the pressures of a global pandemic. Recent findings: Although cardiac rehabilitation has been shown to result in a mortality benefit, research continues to enumerate the benefits of cardiac rehabilitation to patient function and quality of life in a growing range of cardiovascular diseases. In addition, new methodologies and new models of cardiac rehabilitation have emerged with the goal of increasing patient referral and participation. Summary: Cardiac rehabilitation continues to evolve and adapt to serve a growing and diversifying number of patients with cardiovascular disease with the goal of both decreasing mortality and improving patient function.